La deuda externa en Ecuador: un análisis del impacto económico durante los dos boom petroleros; 1972-1980, 2008- 2017 - Coello Santacruz, Juan Andrés (2025)
This research analyzes the economic, political, and social effects of external debt in Ecuador during the oil boom periods of 1972-1980 and 2008-2017. These periods correspond to two periods of economic growth driven by oil revenues and by a strong dependence on external credit. This dependence allows us to study the country's economic structure and its vulnerability to fluctuations in international oil prices. The research employs a mixed-methods approach, combining historical and documentary analysis with a quantitative study of macroeconomic indicators obtained from national and international sources. This combination facilitates the analysis of the evolution of external debt and its connection to the economic policies implemented during the corresponding periods. During the first oil boom (1972-1980), which occurred under military governments, external credit was directed toward infrastructure projects and public works to promote national modernization. In contrast, during the second oil boom (2008-2017), debt was used for social purposes related to strategic infrastructure, a period marked by limited transparency and centralized power that revealed a lack of clarity in economic management. The results show that, across different lenders, external debt increased exponentially during both boom periods. Despite revenue growth in the oil sector, it did not alter the national productive structure, nor did it help reduce dependence on oil. This led to a heavy reliance on foreign loans and a persistent budget deficit driven by current government spending. Furthermore, the research reveals that external debt is a political instrument used to finance public policies based on politicians' patronage, thereby reinforcing their terms in office and legitimizing them, at the expense of the country's long-term economic sustainability. The research emphasizes the need for responsible and ethically transparent external debt management, geared towards economic diversification to reduce vulnerability to international oil prices and ensure long-term financial sustainability.